Analisis kesopanan berbahasa dalam novel Melunas Rindu / Sara Beden - Sara, Beden (2016)
This study is related to the aspect of language politeness based on the Melunas Rindu novel which is a literature text used by the Form 4 students in Zone 4 (Johor, Sabah, Sarawak and Wilayah Persekutuan Labuan) Malaysia. The analysis of the data in this study involves 33 speech events based on the dialogues of Fuad, the main character and Farhana, the supporting character. The problem of the study stems from the issues of the increase in language politeness erosion and limited references at the academic level. Limitation and lack of studies on literature materials that is being analysed pragmatically also encourages this study. This study consists of three objectives; to classify the language politeness patterns, to analyse the pattern of language politeness and to map of the speech event structures in Melunas Rindu novel. The results of the study will provide a new input with a value added, namely literature material is scrutinized from a higher thinking perspective using the linguistic theory. This study also contributes towards enriching material in pragmatic besides fulfilling the dearth of studies using literature materials. Subsequently, this study will confer the communication procedures to the targeted audiences to practice into their lives.This study has employed the library research, text analysis and quantitative method. This study has applied two theories; Leech’s model of Politeness Principle (1983) and Grice’s model of Cooperation Principle (1975) to form the General Maxim Combination Pattern Model (MPKMU). The General Maxim Combination Pattern Model consist of six maxim combination patterns; Pattern 1, 6 PS + 4 PK; Pattern 2, 5 PS + 3 PK; Pattern 3,4 PS + 2 PK; Pattern 4, 3 PS + 1 PK; Pattern 5, 2 PS and Pattern 6, 1 PS, which is used as a basis to analyse the data. Through the analysis done all the three objectives in this study had been accomplished. The results showed 33 events in Melunas Rindu can be classified in vi the MPKMU based on the principle of almost similar, accurate and economical. Pattern 1 represented by 93 dialogues (42.09%), Pattern 2 represented by 112 dialogues (50.68 %), whereas Pattern 3 and 4 represented by 4 dialogues (1.80 %) respectively , Pattern 5 represented by 7 dialogues (3.17 %) and the final pattern, Pattern 6 represented by 1 dialogue ( 0.46 %).The results based on MPKMU has shown the highest usage was Pattern 2 which conform to 17 events (50.68 %) and the lowest usage was Pattern 6 which conform to 1 event (0.46 %.). Besides that, the results showed compliance of Pattern 1 and 2 to almost the same principle, Pattern 3 and 4 compliance to economical principle and compliance of Pattern 5 and 6 to accurate principle. The analysis of total number of maxims and dialogues exhibit five variations based on the factor of context. The context analysis has shown 20 events (60.6 %) on existence of context are significant while 12 events (36.4%) exhibit existence of context which are insignificant. While, one event (3.00 %) disclosed context preparation of Ø. The results showed that context is not a mandatory need to exist in a given speech event. Complete information in a speech event also depends on the compatibility between discussed topic with the application and selection of the language elements. The results of the mapping event structures has disclosed variation of structures are based on factors of context, background and topic due to the need of creating a conflict free situation which coincide with the objective of communication. In conclusion, use of the combined theories, Leech’s (1983) and Grice’s (1975) could specify comprehensively language politeness in the Melunas Rindu novel.